Dimer-dimer interaction of the bacterial selenocysteine synthase SelA promotes functional active site formation and catalytic specificity - Itoh, Yuzuru (J Mol Biol, 2014)
The 21(st) amino acid, selenocysteine (Sec), is incorporated translationally into proteins, and is synthesized on its specific tRNA (tRNA(Sec)). In Bacteria, the selenocysteine synthase SelA converts Ser-tRNA(Sec), formed by seryl-tRNA synthetase, to Sec-tRNA(Sec). SelA, a member of the fold-type-I pyridoxal 5′-phosphate (PLP)-dependent enzyme superfamily, has an exceptional homodecameric quaternary structure with a molecular mass of about 500 kDa. Our previously determined crystal structures of Aquifex aeolicus SelA complexed with tRNA(Sec) revealed that the ring-shaped decamer is composed of pentamerized SelA dimers, with two SelA dimers arranged to collaboratively interact with one Ser-tRNA(Sec). The SelA catalytic site is close to the dimer-dimer interface, but the significance of the dimer-pentamerization in the catalytic site formation remained elusive. In the present study, we examined the quaternary interactions, and demonstrated their importance for SelA activity by systematic mutagenesis. Furthermore, we determined the crystal structures of “depentamerized” SelA variants with mutations at the dimer-dimer interface that prevent pentamerization. These dimeric SelA variants formed a distorted and inactivated catalytic site, and confirmed that the pentamer interactions are essential for productive catalytic site formation. Intriguingly, the conformation of the non-functional active site of dimeric SelA shares structural features with other fold-type-I PLP-dependent enzymes with native dimer or tetramer (dimer-of-dimers) quaternary structures.